Comparison of Three Agarose Based Chelating Adsorbents and Their Application to the Preconcentration of Some Metal Ions in Water - Akhlaghi, Hashem; Hashemi, Payman; Boroum, Jafar; Ghafurian, Hossain (Asian Journal of Chemistry, 2016)
The properties of two agarose based chelating ion exchangers with, respectively, dipicolyl amine (DPA) and tris(2-aminoethyl) amine (TREN) as functional groups are investigated and compared to those of a previously studied adsorbent functionalized with iminodiacetic acid (IDA), with the same matrix, for preconcentration of Cu, Co and Ni in water. Binding capacities, adsorption rates and column recoveries of the metal ions are carefully investigated. An ICP-AES instrument is used for measurements. The capacity of the IDA adsorbent for Cu, Co and Ni was similar and is averaged to 50 (± 7) μmol/mL, while for the DPA and TREN sorbents the capacity was more variable and pH-dependent. The highest capacity of the new adsorbents was obtained for copper, which is averaged to 18.3 (± 0.3) and 120 (± 6) μmol/mL, respectively. Kinetic studies indicated relatively high adsorption rates of Cu on all the sorbents. Nickel, on the other hand, showed relatively slow rates on the DPA and TREN chelators. High column recoveries were obtained for all the studied metal ions on the IDA adsorbent and only some loss of Ni was observed at high pHs. The column recoveries for the DPA sorbent, on the other hand, were quite low for Cu and Ni. It indicated high recoveries only for Co, which rose up to 93.8 (± 1.8)%. Copper was almost quantitatively recovered on the TREN sorbent, with low and pH dependent recoveries for Co and Ni. The method was evaluated by preconcentration of spiked river water samples. Good agreement was obtained between the results obtained for natural samples and standard solutions. In general, more selectivities, slower adsorption rates and lower and more pH dependent recoveries were identified for the DPA and TREN sorbents compared to that with the IDA groups.